Partilha de polinizadores por espécies quiropterófilas em um fragmento de Cerrado, São Paulo - Teixeira, Reinaldo Chaves (2010)
Flowering plants need some external pollen vectors to accomplish sexual reproduction. For plants, the access of sexual mates by pollinators agents is a limiting factor, wich make pollen vectors a critical resource for plants to reproduce successfully. Simpatric plants that share the same pollination guild avoid direct competition differing the pollinators use mode. These thesis investigate in a cerrado community the coexistence mechanisms between plant species that use the same pollinators guild, the bats. The work was carried out in a cerrado area in Brazilian southeast, between July, 2007 and June, 2009. First of all, I assessed the chiropterophilous species composition in the area, describe the floral biology and the interactions with their flower visitors. I found nine species framed in the chiropterophily syndrome, and which the flowers received visits mainly from the bat Glossophaga soricina (except in Irlbachia alata). The species flowers are adjusted to the bats morphology, ethology and physiology, and offer flowers all year long, assuring food for the bats. Then I verify the mechanisms that allow the chiropterophilous species coexistence or the facilitative interactions in the area by pollinators share. I assess the floral characteristics, blooming phenology, nectar attributes and floral visitors. Nine plant species share similar floral characteristics that are noted by the bats sense, which play as facilitative interaction between species, which produces a single floral display for attract the pollen vector in common. However, the plant species differ in the places for pollen deposition in the bats body due to differing in floral morphology, species offered distinct nectar volume and concentration which may select/segregate the pollinator and share the pollinator use during the year by flowering at different moments, which allows species that share pollinators to coexist. At last, I checked how two species in the same genus and that use the same bats as pollinators differ in the way to use the same pollen vector. I estimate the bats role in the plants species floral biology and if the species differ in floral characteristics, nectar attributes and secretion time, flowering period. I verified that group - flowers with different size shall avoid pollen mixture among species, nectar with distinct soluble concentration shall attract higher number of visitors in distinct moments, massive flowering in different periods and sequentially, allows the Bauhinia holophylla and B. longifolia coexistence in the area, even sharing the G. soricina use as main pollinator.